Influence of Combined Application of Inorganic N and P Fertilizers and Chicken Manure on Quality and Shelf-Life of Garlic (Allium sativum L.) Bulbs - Shiferaw, G Diriba; Dechassa, R Nigussie; Kebede, Woldetsadik; Getachew, Tabor; Sharma, J J (Journal of Postharvest Technology, 2016)
Crop quality and shelf-life improvement with soil fertility maintenance requires a  balanced application of inorganic and organic nutrient sources. Thus, a field  experiment was conducted to investigate the effect of chicken manure (CM)  combined with reduced levels of nitrogen and phosphorus fertilizers on garlic  quality and shelf-life at Debre Zeit Agricultural Research Centre, Ethiopia, on two  soil types (Andosols and Vertisols). The treatments consisted of factorial  combinations of three levels of nitrogen (0, 46 and 92 kg N /ha), three levels of  phosphorus (0, 20 and 40 kg P /ha) and three levels of chicken manure (0, 10 and  20 t CM /ha). The treatments were laid out in a randomized complete block design  with three replications at each soil type. Results showed that the main effects of  nitrogen, phosphorus, chicken manure and soil type had a positive and significant  effect on the evaluated quality parameters in the experiments. The effect of the  manure on shelf-life and qualities of garlic bulb were significantly higher in both  soils than the mineral N and P fertilizers, but the highest quality of garlic bulb was  recorded on Vertisols than on Andosols. The interactions of the appliedQuality, shelf life and mineral contents of garlic bulbs were significantly influenced by the  interaction effect of fertilizers; the better values being obtained with the combined  application of 46 kg N /ha, 20 kg P /ha and 20 t CM /ha on both soils. However, the  highest bulb qualities were obtained in the combined application of 46 kg N, 20 kg  P and 10 t CM /ha on Andosols. Thus, application of 10 or 20 t /ha CM resulted in  a saving of 50% of the recommended levels of both inorganic N and P fertilizers,  without reducing the bulb quality of garlic.   fertilizers  also significantly influenced the quality traits of garlic on both soils
Keywords: Bulb quality; Inorganic fertilizer; Chicken manure; Shelf-life; Soil type